Intercultural Communication for the Foreign Students’ Adjustment in Governed Universities in Northern Region - Punpong, Akkarong; Khamnamkoo, Paranyoo (Humanities and Social Sciences Journal of Pibulsongkram Rajabhat University, 2023)
The purposes of this research were to study the communication competence for self-adaptation and the way to communication of the foreign students at Governed Universities in northern region. This study employed qualitative research techniques being collected by in-depth interview and focus group from 15 foreign students who study in northern region universities. The results were as follows: 1) The respondents decided to study in Thailand because of recognizing education easy visa, university fee, avoiding the highly competitive education in home country, career opportunities, and fondness of Thai people /climate/landscape/food/culture/tradition. 2) There was relationship found between communication competence and self-adaptation for the foreign students at governor ‘s university in northern region. Most foreign students already had a good background in English but there was problems with use of Thai language and the adaptation to local life. By the way, they used communication technology (internet, social media, smartphone) to helped in adaptation process for communication competence such as Google Translate. 3) The way for the foreign students to adjust were to tried to study new Thai language/culture/tradition, being open-minded, thinking positive and accepting differences in ethnic/nationality/religion and culture.